Experimental observation of brillouin linewidth broadening and decay time in photonic crystal fiber - Beugnot, J. C.; Stiller, Birgit; Foaleng Mafang, S.; Lee, M. W.; Delque, M.; Kudlinski, A.; Maillotte, H.; Laude, V.; Thevenaz, L.; Sylvestre, T. (European Conference on Optical Communication, ECOC, 2010)
We present a novel distributed sensing technique that makes possible the observation of Brillouin gain spectral distribution and acoustic decay time in photonic crystal fiber as well as in standard single-mode fiber. ©2010 IEEE.
CRIS-Team Scopus Importer:2021-06-29